2022
DOI: 10.1021/acsomega.2c02958
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Assisted Sensing of Trinitrotoluene by Optical Array

Abstract: Here we report the design and fabrication of an array-based sensor, containing functionalized Carbon Dots, Bodipy’s and Naphthalimide probes, that shows high fluorescence emissions and sensitivity in the presence of low amounts of TNT explosive. In particular, we have fabricated the first sensor device based on an optical array for the detection of TNT in real samples by using a smartphone as detector. The possibility to use a common smartphone as detector leads to a prototype that can be also used in a real-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In recent years, nanomaterials have been widely used for the chemical sensing of many species [ 32 , 33 , 34 , 35 ]. In particular, cortisol sensing by nanostructured species can be performed by different classes of nanosystems: gold nanoparticles, carbon nanoparticles, graphene oxide, metal nanoflowers, nanowires, nanoflakes, and metal nanorods.…”
Section: Nanomaterials For Sensingmentioning
confidence: 99%
“…In recent years, nanomaterials have been widely used for the chemical sensing of many species [ 32 , 33 , 34 , 35 ]. In particular, cortisol sensing by nanostructured species can be performed by different classes of nanosystems: gold nanoparticles, carbon nanoparticles, graphene oxide, metal nanoflowers, nanowires, nanoflakes, and metal nanorods.…”
Section: Nanomaterials For Sensingmentioning
confidence: 99%
“…There is a general perception among the common people about the explosive nature of TNT and through the print as well as electronic media we are more familiar with the term TNT [ [39] , [40] , [41] , [42] , [43] ], but 2,4,6 trinitrophenol by no means exhibits lesser potential as an explosive compared to TNT [ 44 , 45 ]. Therefore, designing a suitable chemosensor that can effectively detect TNP has extreme importance in the field of forensic science.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial olfactory system, also called the electronic nose (E-nose), which consists of a sensor array with pattern recognition, has been developed to mimic the mammalian olfactory system for ETD. Some kinds of sensor arrays have been designed, such as a multichannel colorimetric sensor array, , optoelectronic nose, effect transistors, , and chemiresistors. , Zhao et al designed a dynamic multichannel colorimetric sensor array; the sensor array exhibited different absorption peaks at 456, 504, 552, 612, 754, and 906 nm; then 10 kinds of explosives can be discriminated based on it; and the detection limit achieved 1.5 μM . Askim et al reported an optoelectronic nose consisting of 40-element to distinguish several explosives and related compounds in the gas-phase, and the resulting 14 out of 16 groups achieved 100% accuracy .…”
Section: Introductionmentioning
confidence: 99%